A study of the types and manifestations of physicians' unintended behaviors in the DRG payment system - Wei-Fu Chang; Wei-Fu Chang; Wei-Fu Chang; Xin-Yu Yan; Xin-Yu Yan; Hao Ling; Ting Liu; Ai-Jing Luo; Ai-Jing Luo (Frontiers Media S.A., 2023)
IntroductionIn recent years, China has implemented the Diagnosis Related Groups (DRG) payment system as part of its healthcare insurance reimbursement policy. Numerous studies have focused on the effectiveness of DRG payment system in controlling unreasonable growth in medical expenses. However, there has been no systematic report on the types of unintended behaviors exhibited by doctors under the DRG payment system.MethodsThe study first utilized interrupted time series analysis to analyze medical records and insurance data from eight hospitals. It investigated the data changes in MDC and ADRG groups before and after the implementation of the DRG payment system. Subsequently, a semi-structured interview method was employed to conduct qualitative research on the unintended behaviors of physicians, aiming to gain a more accurate understanding of specific changes in physician behavior after the implementation of the DRG payment system.ResultsThis study discovered that doctors engage in unintended behaviors within the framework of the DRG payment system.DiscussionIn the early implementation of the DRG payment system in China, the contradictions between the flawed DRG payment methods and supporting systems and the actual diagnostic and treatment work manifested in the form of unintended doctor behaviors. Most of these unintended behaviors can be considered reasonable feedback from doctors to cope with the existing system flaws. They are conducive to identifying the deficiencies in China's DRG payment system and suggesting directions for improvement.